2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20172211
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling vs. chemical reconstructon of skin scars with trichloroacetic acid: a comparative study

Abstract: <p class="abstract"><strong>Background:</strong> Acne scars are a cause of major psychological morbidity in the young population. Microneedling using dermarollers which uses the principle of percutaneous collagen induction and Chemical reconstruction of skin scars (CROSS) using Trichloroacetic acid (TCA) are both widely used methods for the treatment of acne scars and are cheaper alternatives to LASER resurfacing. The aim of our study is to objectively compare the efficacy of microneedling us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Microneedling with either derma-pen or dermaroller combined with various chemical peels and other agents like platelet rich plasma (PRP) and glycolic acid has been researched extensively to find out the right combination with best results. [11][12][13] We also used such a combination that included microneedling with dermaroller, alternating with a medium depth chemical peel 30% TCA and the results have turned out be highly significant for improvement in acne scar grading from baseline. The improvement was observed more in the acne scars having grade IV at baseline (week=0) as compared to the ones having grade III.…”
Section: Discussionmentioning
confidence: 99%
“…Microneedling with either derma-pen or dermaroller combined with various chemical peels and other agents like platelet rich plasma (PRP) and glycolic acid has been researched extensively to find out the right combination with best results. [11][12][13] We also used such a combination that included microneedling with dermaroller, alternating with a medium depth chemical peel 30% TCA and the results have turned out be highly significant for improvement in acne scar grading from baseline. The improvement was observed more in the acne scars having grade IV at baseline (week=0) as compared to the ones having grade III.…”
Section: Discussionmentioning
confidence: 99%
“…Boxcar and rolling scars responded well to microneedling and ice pick scars to the CROSS technique. [ 23 ] Ramadan et al [ 24 ] found TCA CROSS to be inferior to subcision in decreasing the size of scars with TCA having more pigmentary alteration. It has been found to have comparable efficacy with 1550 nm Er:glass fractional laser in patients of type IV and V skin.…”
Section: Hemical R Econstruction Of mentioning
confidence: 99%